Deprivasi Tidur dan Disregulasi Nafsu Makan - Raymond R. Tjandrawinata (PT Dexa Medica, 2026)
Sleep deprivation is a biological factor that is often overlooked in appetite regulation. However, growing evidence indicates that disturbances in sleep duration and quality, as well as circadian misalignment can shift hunger–satiety control through hormonal, metabolic, and brain reward system mechanisms. This perspective review discusses the latest evidence regarding the roles of leptin, ghrelin, insulin, stress hormones, circadian rhythms, and chrononutrition in the association between sleep and appetite, highlighting its clinical relevance for general medical practice in the prevention and management of metabolic disorders.